Preliminary study of solute carrier family 23 member 3 (SLC23A3) gene as candidate marker for fatty acid traits in Kampung-Broiler crossbred chickens - A. Gunawan; S. Y. Basril; K. Listyarini; A. Furqon; W. Bilyaro; J. Jakaria; M. J. Uddin; C. Sumantri (Diponegoro University, 2018)
SLC23A3 is one of the key genes which control the properties of the of fatty acids content in the meat. The aim of this study was to identify the association of SNP and mRNA expression of SLC23A3 as a candidate marker for fatty acid traits (FAs). Sixty two F2 Kampung × Broilers crossbred chickens population were used in this study. FA composition was measured at 12 weeks of age from thigh meat of crossbred chicken. The PCR-RFLP and qRT-PCR were used for association study and expression analysis of SLC23A3 gene with divergent fatty acid composition. A SNP in coding region c.22385690 A>C of the SLC23A3 gene was associated (P<0.05) with fatty acid composition including stearic acid (C18:0), elaidic acid (C18:1n9t), and linoleic acid (C18:2n6c). The SLC23A3 was detected in liver from high fatty acids (HFA) and low fatty acid (LFA) composition. However, gene expression of SLC23A3 were not differentially expressed between HFA and LFA. These results will explain better understanding of the key important role of the SLC23A3 in fatty acid traits within the liver and will propose SLC23A3 as a potential genomic selection for selection of chickens with fatty acid composition.